Systematic Literature Review: The Obstacles of Madrasah Aliyah Students Facing Maharatul Qiraah - Robithah Aulia; Sofyan Sauri; Asep Sopian (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
Reading proficiency is one of the important aspects of language learning. Arabic language assessment is also assessed through the individual's reading proficiency. Obstacles found in one Arabic language learning proficiency are aspects that need to be considered. Students experience obstacles that affect their learning achievement. Having an in-depth identification of the problems of maharah qiraah will make it easier for teachers to teach Arabic. This study uses a qualitative approach with a systematic literature review method. Data sources are obtained from the results of research conducted by other researchers. This is done so that researchers can access more information about the problems of maharah qiraah. To produce relevant research, researchers select articles published in the last five years. Data search uses